High specific torque motor for propulsion system of aircraft - Golovanov, Dmitry; Galea, Michael; Gerada, C. (2016)
This paper proposes an analytical model that considers the torque characteristics for high specific torque synchronous machine with outer rotor and a Halbach permanent magnet array. The distribution of the magnetic field in the air gap is obtained with a linear assumption by solving Neumann’s problem. The analytical model presented in the paper allows preliminary estimation and fast optimization of the machine’s geometry and can be used to develop a first cut design of the machine. The application of the analytical model proposed is demonstrated via the adaptation and modification of a traction machine designed for electrical taxiing to a machine for propulsion of electric aircraft.